The Covenanters of Damascus; A Hitherto Unknown Jewish Sect - Moore, George Foot (Harvard theological review, 1911)
Among the Hebrew manuscripts recovered in 1896 from the Genizah of an old synagogue at Fostat, near Cairo, and now in the Cambridge University Library, England, were found eight leaves of a Hebrew manuscript which proved to be fragments of a book containing the teaching of a peculiar Jewish sect; a single leaf of a second manuscript, in part parallel to the first, in part supplementing it, was also discovered. These texts Professor Schechter has now published, with a translation and commentary, in the first volume of his Documents of Jewish Sectaries. The longer and older of the manuscripts (A) is, in the opinion of the editor, probably of the tenth century; the other (B), of the eleventh or twelfth.